The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1371/journal.pone.0227109
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a live-attenuated small-colony variant improves the humoral and cell-mediated responses against Staphylococcus aureus

Abstract: Staphylococcus aureus is known to produce persistent and chronic infections in both humans and animals. It is recognized that small-colony variants (SCVs), which produce higher levels of biofilm and that are capable of intracellular persistence, contribute to the chronicity or recurrence of infections and that this phenotype is inherent to the pathogenesis process. Prevention of S. aureus infections through vaccination has not yet met with considerable success. Some of the current vaccine formulations for S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…3A, B, Ca); which may be similar to that reported in S. aureus small colony variants (SCVs) [68,69]. SCVs are slow-growing, drug-resistant mutants of gram-positive and -negative bacteria, and have been isolated during the longterm treatment with antimicrobial agents, such as gentamicin and trimethoprim-sulfamethoxazole (SXT); SCVs cause persistent and recurrent infections [68,[70][71][72], and examples include our reported case, daptomycin-resistant VISA SCV [69]. Therefore, the sticky intercellular substance may play a role in low-level vancomycin resistance.…”
Section: Resultssupporting
confidence: 68%
“…3A, B, Ca); which may be similar to that reported in S. aureus small colony variants (SCVs) [68,69]. SCVs are slow-growing, drug-resistant mutants of gram-positive and -negative bacteria, and have been isolated during the longterm treatment with antimicrobial agents, such as gentamicin and trimethoprim-sulfamethoxazole (SXT); SCVs cause persistent and recurrent infections [68,[70][71][72], and examples include our reported case, daptomycin-resistant VISA SCV [69]. Therefore, the sticky intercellular substance may play a role in low-level vancomycin resistance.…”
Section: Resultssupporting
confidence: 68%
“…Two mastitis vaccine candidates against S. uberis have shown a significant reduction in the mortality of mice infected with the pathogen (83). Different candidates for a S. aureus vaccine is currently being investigated; in one study, live-attenuated small-colony variants have shown promising results compared to inactivated bacteria in murine models (84). However, in another study, a formalin-killed whole-cell vaccine candidate of S. aureus biofilm showed a significant reduction in the colonization of S. aureus in the udder in vaccinated mice compared to mice vaccinated with a vaccine candidate from planktonic S. aureus (85).…”
Section: Potential Vaccines Against Biofilm Forming Mastitis Pathogensmentioning
confidence: 99%
“…Most of the so-called in vivo investigations of biofilm in bovine mastitis have used experimental models (mice and sheep), and the majority of these studies focused on anti-biofilm treatment or vaccines against biofilm udder infections (Table 1) (44,69,70,72,(83)(84)(85). Only a few studies investigated and confirmed biofilm in vivo within udder tissue of dairy cows with bovine mastitis.…”
Section: In Vivo Investigations Of Biofilm In Bovine Mastitismentioning
confidence: 99%
“…The low intracellular bioavailability and cellular permeability of antibiotics also promote the antibiotic resistance of intracellular pathogens [23,24]. The formation of a low metabolically active small colony variant (SCV) S. aureus phenotype enables it to be less susceptible to antibiotics [25,26]. S. aureus can also form biofilms that promote the survival and persistence of the pathogen in harsh conditions and also provide antibiotic resistance by limiting antibiotic penetration [27,28].…”
Section: Introductionmentioning
confidence: 99%